Novel therapeutic options in inflammatory cardiomyopathy (Swiss Medical Weekly, 2013)
Inflammatory dilated cardiomyopathy (iDCM) denotes cardiac dysfunction due to myocardial inflammation (myocarditis). Progressively impaired cardiac contractility, fibrosis and dilation of heart chambers characterise iDCM phenotypically, and are associated with poor clinical prognosis. Cardiotropic infections followed by autoimmune responses against heart tissue are the most common cause of iDCM. The pathophysiology of iDCM is still poorly understood. Nevertheless, our understanding of the molecular mechanisms of inflammatory heart failure advanced during recent years. In fact, recent mechanistic insights might open the view for novel diagnostic and therapeutic approaches for iDCM patients in the future. In this review we update our knowledge on disease mechanisms, summarise current clinical approaches for iDCM patients, and discuss future therapeutic options.